Bacterial diversity changes in response to an altitudinal gradient in arid and semi-arid regions and their effects on crops growth - Zakavi, Maryam; Askari, Hossein; Shahrooei, Mohammad (Frontiers in Microbiology, 2022)
The microbiome of soil has a fundamental role in maintaining the health of soil and plants. While the diversity of microbes is one of the most important factors in the environment, little is known about the effects of elevation on the microbiome and the impact of the affected microbiome on plants. The main goal of this study is to expand our knowledge of what happens to the soil bacterial community along an altitudinal gradient and investigate their possibly different impacts on plant growth. Bacteria from soils at various altitudes have been isolated, characterized, and identified by Matrix-Assisted Laser Desorption/Ionization-Time of Flight Mass Spectrometry (MALDI-TOF MS) to determine the effects of an elevational gradient on the microbiome and plant growth. Furthermore, their effects have been investigated by isolates assessment on maize, wheat, and canola. Based on our results, higher altitude results in a higher diversity of the microbiome and lower bacteria biomass. Bacillus cereus is found in abundance in arid and semi-arid samples. Interestingly, enhanced diversity in higher altitudes shows similarity in response to environmental stress and tolerates these factors well. Furthermore, the inoculation of these bacteria could enhance the overall growth of plants. We prove that bacterial communities could change their biomass and diversity in response to altitude changes. These indicate evolutionary pressure as these bacteria could tolerate stress factors well and have a better relationship with plants.